Volume 1: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53524
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Spatial and Temporal Aspects of the Liquid Fuel Placement in a Swirl Cup at Elevated Pressure

Abstract: The kerosene spray generated by a pressure swirl fuel nozzle embedded in a swirling airflow in a swirl cup typical of aeroengine combustors was investigated at different levels of air pressure to assess the counter-acting effects of increasing air density and transfer of centrifugal momentum from airflow to spray. Hardware parameters investigated included air swirl angle and fuel nozzle flow number. Measurement techniques included spray visualization, Phase-Doppler Anemometry (PDA) for spray analysis and Laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Wang et al 5 studied the hardware design of the flow field structure and found that the flare influenced the size of the recirculation zone and droplet dispersion. Becker and Hassa 6 and Shanmugadas et al 7 studied the fuel placement and droplet size inside the swirl cup using PDI and PLIF. They highlighted that swirl shear layers should be considered in fuel injector designs for improving atomization and interactions between fuel and the air shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 5 studied the hardware design of the flow field structure and found that the flare influenced the size of the recirculation zone and droplet dispersion. Becker and Hassa 6 and Shanmugadas et al 7 studied the fuel placement and droplet size inside the swirl cup using PDI and PLIF. They highlighted that swirl shear layers should be considered in fuel injector designs for improving atomization and interactions between fuel and the air shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ambient pressure and temperature on the spray structure of the pressure swirl and airblast sprays has been investigated in several previous studies [5][6][7][8][9][10][11][12]. In most of these investigations, the external spray structure and drop size variation are captured at various operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The pilot stage of the lean-burn injector is a typical swirl cup design which uses a pressure swirl atomizer with two coaxial, counter-rotating swirlers to atomize the fuel. The spray of swirl cup have been studied by many researchers, [10][11][12][13][14] most of the works center on flow structure. Indeed, only few experiments are preformed to characterize the spray.…”
Section: Introductionmentioning
confidence: 99%